Gender Issues in Early Childhood Education in Indonesia: A Psychological Perspective - Ni Luh Drajati Ekaningtyas (IAHN-TP Palangka Raya, 2023)
The high level of gender bias coupled with the large number of cases of gender-based violence that have occurred illustrates the dismal portrait of gender equality in Indonesia. This gender bias treatment can occur in all age groups, including in early childhood. This study aims to analyze issues related to gender in early childhood with a psychological approach. This research is a library research or literature study that begins with initial data collection for the formulation of research problems, research data collection, data evaluation, problem analysis with reference to the literature, and drawing conclusions. The results of the study illustrate that gender issues in early childhood include parenting in the family, management of early childhood education institutions, as well as learning processes and play activities. Treatment that is gender biased from early childhood will affect the future development of children, so that the active role of various parties is needed to seek to provide stimulation of growth and development in early childhood that is free from gender bias.